An atypical case of partial displacement and wash-out of the mineral trioxide aggregate-based sealer in endodontic surgery - Guiotti, Flávia Angélica [UNESP]; Kuga, Milton Carlos [UNESP]; Magro, Miriam Graziele [UNESP]; Venção, Ana Carolina [UNESP]; Tonetto, Mateus Rodrigues; Jordão-Basso, Keren Cristina Fagundes [UNESP]; Bandeca, Matheus Coêlho; Dantas, Andrea Abi Rached [UNESP] (Jaypee Brothers Medical Publishing, 2015)
This clinical report described an atypical case where the mineral trioxide aggregate (MTA)-based sealer added with 20% calcium hydroxyde was used for retrograde filling. The patient was subjected to endodontic surgery to remove persistent apical lesion. After the apicoetomy and apical cavity preparation using an ultrasonic device, MTA-based sealer (MTA Fillapex) added with 20% calcium hydroxide (w/w) was used for retrograde filling. After 48 hours, the radiographic analysis showed partial displacement and wash-out of sealer. The case was only clinically controlled and no surgery was performed. After 10 months, the postoperative control showed reduction of periapical radiolucent image and absence of symptoms, radiographic and clinical signs, presented bone periradicular repair showing partial absence of the sealer in cavity retrograde.
Keywords: Calcium hydroxide; Calcium release; Endodontics; Flow MTA; pH; Surgery